Blood contamination, a problem or a lucky chance to analyze non-invasively Myokines in mouth fluids? - Ravara, Barbara (Eur J Transl Myol, 2019)
Use of saliva in clinical studies are increasing to identify methods less invasive than blood sampling in search for systemic changes of biomarkers related to physical activity, aging, late aging and rehabilitation. The consensus is that the diagnostic value of whole saliva is compromised by the presence of blood, but we are looking at the contamination as a major opportunity for non-invasive analyses of serological biomarkers. The aim of this preliminary study was to evaluate the presence of serum in mouth fluids of healthy seniors and the eventual changes after a modest trauma, i.e., tooth brushing. Seven heathy persons, aged more than 65 years, drooling saliva in a test tube provided the fluids for the analyses. After low speed centrifugation, small aliquots of supernatants were frozen in liquid nitrogen and stored at -80° until use. Aliquots were thawed and used for quantification by the Lowry method of total proteins and by colorimetric ELISA of serum albumin, fibrinogen and lysozyme. Hemoglobin content was quantified by Spectrophotometry. Adjustment of saliva dilution, after a preliminary test, increased the homogeneity of the analytes’ content determined by colorimetric ELISA. The control reference to judge the quantity of serum in saliva was a pool of sera from age-matched healthy persons. Saliva collected from the seven healthy elderly person before and after tooth-and-gum, brushing presented measurable amount of the analytes, including fibrinogen, a minor component of the pooled sera. Tooth brushing did not induced statistically significant difference in analytes’ contents, suggesting that a measurable blood contamination is a frequent event in elderly persons. In conclusion, fibrinogen analysis in saliva is a promising approach to quantify serological biomarkers by a non-invasive procedure that will increase acceptability and frequency of analyses during follow-up in aging and rehabilitation.